NATO'S ROLE IN SETTLEMENT OF INTERNATIONAL CONFLICTS (Вісник: Міжнародні відносини, 2022)
The article analyzes the role of the NATO in resolving international conflicts, as well as offers proposals for developing a model of cooperation between Ukraine and NATO against the background of Russian aggression.
Keywords: NATO, international organization, international conflict, strategy, aggression, security